Conformance evaluation of the top‐100 Ethereum token smart contracts with Ethereum Request for Comment‐20 functional specifications - Hyeon‐Ah Moon; Sooyong Park (IET Software)
Abstract This study is an attempt to evaluate the compliance problem regarding the current status of the establishment of agreed‐upon interfaces for tokens, which are the most important type of applications of the Ethereum blockchain. The authors analysed the existing application programming interface standard interface called Ethereum Request for Comment 20 (ERC‐20), proposed functional ERC‐20 specifications, and evaluated the real‐world token smart contracts that have been deployed and used for transactions on a blockchain. For the evaluation, the authors developed an automatic tool with a test suite based on the proposed functional specifications. The authors' experiment revealed that no top‐100 market capitalization token smart contracts turned out to agree perfectly based on the functional specifications. In addition, the authors found the de facto standard behaviour deduced through testing with the functional specifications and suggested a possible countermeasure for the compliance problem in dealing with multiple tokens together.